2020
DOI: 10.1038/s41598-020-72943-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine (ADMA) accelerates renal cell fibrosis under high glucose condition through NOX4/ROS/ERK signaling pathway

Abstract: We previously reported that the circulatory level of Asymmetric dimethylarginine (ADMA), an endogenous competitive inhibitor of nitric oxide synthase, was increased in diabetic kidney disease patients. However, the mechanism and the role of ADMA in diabetic kidney injury remain unclear. Hence, our principal aim is to investigate the causal role of ADMA in the progression of renal cell fibrosis under high glucose (HG) treatment and to delineate its signaling alterations in kidney cell injury. High Glucose/ADMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Another study demonstrated that decreasing renal ADMA production by inhibiting type I PRMTs exacerbated renal fibrosis in UUO mice compared to control UUO mice. Interestingly, the addition of ADMA to NRK-49F cells treated with TGF-β reduced fibrosis, in contrast to the aforementioned study using the same cell line at an equal concentration of ADMA (100 μM) [119,123]. Evidently, there is much uncertainty to the role of ADMA with respect to renal fibrosis and kidney disease.…”
Section: Mechanisms For the Progression Of Ckdmentioning
confidence: 81%
See 2 more Smart Citations
“…Another study demonstrated that decreasing renal ADMA production by inhibiting type I PRMTs exacerbated renal fibrosis in UUO mice compared to control UUO mice. Interestingly, the addition of ADMA to NRK-49F cells treated with TGF-β reduced fibrosis, in contrast to the aforementioned study using the same cell line at an equal concentration of ADMA (100 μM) [119,123]. Evidently, there is much uncertainty to the role of ADMA with respect to renal fibrosis and kidney disease.…”
Section: Mechanisms For the Progression Of Ckdmentioning
confidence: 81%
“…While ADMA is implicated in renal fibrosis in CKD, whether it is fibrotic or anti-fibrotic is controversial. In vitro, ADMA was shown to increase cell proliferation, cell migration, and cell invasion of cultured rat kidney fibroblasts (NRK-49F) and mesangial cells, and increased the expression of fibrotic markers in rat kidney fibroblasts [119]. ADMA also induced ROS through upregulation of NOX4 expression, and it was proposed that ROS generated by NOX4 resulted in the phosphorylation of ERK1/2 and the activation of myofibroblasts [119].…”
Section: Mechanisms For the Progression Of Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERK signaling pathway, especially ERK1/2, is closely related to the fibroblast proliferation in cardiac and pulmonary fibrosis [ 77 , 78 ], and inhibition of ERK activity has been shown to attenuate lung injury and inflammation induced by bleomycin in a murine model [ 79 ]. Moreover, activation of ERK signaling is related to the presence of NOX and ROS [ 80 ]. NOX inhibitors have been shown to suppress the activation of ERK1/2 and EMT in human tubular epithelial cells, an effect that was mainly related to the reduction of ROS levels [ 81 ].…”
Section: Pathogenesis Of Ipfmentioning
confidence: 99%
“…The best known example of this group is urea; the high concentration of which leads to an increase of osmotic pressure, impaired nitric oxide synthesis, proinflammatory endothelial dysfunction and apoptosis, and death of smooth muscle cells [9][10][11]. Other substances, such as guanidine, may competitively inhibit NO synthase and contribute to the development of hypertension, progression of renal failure and renal fibrosis, and to adverse cardiovascular events and increased mortality in patients with renal failure [12][13][14].…”
Section: Uremic Toxins and Ckdmentioning
confidence: 99%